Alginate Profile, Antioxidant, and Antibacterial Activities of Brown Algae Sargassum cristaefolium from Pane Island, North Sumatera - Astrid Fauzia Dewinta; Ipanna Enggar Susetya; Khairunnisa Khairunnisa; Mai Suriani; Syahira Addina; Amanatul Fadhilah (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research